Francisella tularensis subsp. holarctica bacteraemia in an immunocompetent male - Niels Schepens; Thessa Verniest; Isabel Verstreken; Liesbet Henckaerts (Respiratory Medicine Case Reports, 2023)
Tularemia is a rare zoonotic disease caused by the two predominant subspecies of Francisella tularensis, namely subspecies tularensis and subspecies holarctica. The latter is less virulent than the former, is endemic in Europe, and usually has a mild disease course, although respiratory involvement and bacteraemia can occur. Tularemia in Belgium is rare, but the incidence seems to be increasing. It therefore seems prudent to raise awareness among clinicians for this potentially severe disease. We report the first case of pneumonic tularemia with bacteraemia from Belgium, and want to recommend including Francisella tularensis in the differential diagnosis of pneumonia when an unfavorable evolution is seen with standard treatment.